Absolute Batman. Vol. 1, Abomination - Snyder, Scott (Absolute Batman, 2026)
As Bruce Wayne investigates the mysterious black site in the waters off Gotham, he reluctantly draws his friends into Batman's dangerous work -- and comes face to face with powerful new enemies. What is happening at this dark facility? What is Alfred's history with Bane, the villain who has arrived in Gotham City to protect Ark M's secrets? And what does it all have to do with the mysterious investor behind JK Industries?